Cinacalcet may improve oxidative DNA damage in maintenance hemodialysis patients: an observational study - AŞICIOĞLU, EBRU; ARIKAN, İZZET HAKKI (SPRINGER, 2014)
Oxidative stress is accepted as a non-classical cardiovascular risk factor in patients on maintenance hemodialysis (HD). The aim of this study was to evaluate the impact of cinacalcet on oxidative stress biomarkers, oxidative DNA damage (8-hydroxy-2'-deoxyguanosine/deoxyguanosine), endothelial function (FMD %) and carotid artery intima-media thickness (CIMT) in HD patients. Forty-two chronic HD patients with secondary hyperparathyroidism undergoing 60 mg/day cinacalcet treatment with a follow-up of 6 months and 38 age- and sex-matched healthy individuals were included in this prospective study. Plasma malondialdehyde (MDA) levels and 8-hydroxy-2'-deoxyguanosine/deoxyguanosine ratio (8-OHdG/dG) were determined as oxidative stress markers. Superoxide dismutase (SOD), paraoxonase (PON), catalase (CAT), carbonic anhydrase (CAN) and glutathione peroxidase (GPx) activities were measured as antioxidants. FMD % and CIMT were assessed by ultrasonography. MDA levels were decreased; SOD, PON, CAT, CAN and GPx activities were increased after 6 months of cinacalcet treatment in HD patients. Although CIMT remained stabile, there was a significant improvement in FMD % as well as a notable reduction trend in 8-OHdG/dG ratio after 6 months of treatment. Our data have demonstrated that cinacalcet improves oxidative stress, genomic damage, endothelial function and increases antioxidant protection in HD patients after 6 months of treatment.
Keywords: Cinacalcet; DNA damage; Hemodialysis; Oxidative stress; CHRONIC-RENAL-FAILURE; INTIMA-MEDIA THICKNESS; ENDOTHELIAL FUNCTION; SECONDARY HYPERPARATHYROIDISM; CARDIOVASCULAR-DISEASE; ALL-CAUSE; RISK; ATHEROSCLEROSIS; DYSFUNCTION; MORTALITY